2002
DOI: 10.1074/jbc.m110454200
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors NF-Y and Sp1 Are Important Determinants of the Promoter Activity of the Bovine and Human Neuronal Nicotinic Receptor β4 Subunit Genes

Abstract: The ␤4 subunit is a component of the neuronal nicotinic acetylcholine receptors which control catecholamine secretion in bovine adrenomedullary chromaffin cells. The promoter of the gene coding for this subunit was characterized. A proximal region (from ؊99 to ؊64) was responsible for the transcriptional activity observed in chromaffin, C2C12, and COS cells. Within this region two cis-acting elements that bind transcription factors Sp1 and NF-Y were identified. Mutagenesis of the two elements indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
(39 reference statements)
1
22
0
Order By: Relevance
“…Several laboratories are actively pursuing this hypothesis, and substantial work has revealed a number of shared regulatory features between the two genes. First, by using in vitro approaches, it has been shown that the ␣3 and ␤4 promoters can directly interact with and be trans-activated by the widely expressed transcription factors Sp1 and Sp3 (56,59,62,65,70). This observation extends to the third gene in the cluster, the ␣5 subunit gene, which also appears to be regulated by Sp1 (73).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several laboratories are actively pursuing this hypothesis, and substantial work has revealed a number of shared regulatory features between the two genes. First, by using in vitro approaches, it has been shown that the ␣3 and ␤4 promoters can directly interact with and be trans-activated by the widely expressed transcription factors Sp1 and Sp3 (56,59,62,65,70). This observation extends to the third gene in the cluster, the ␣5 subunit gene, which also appears to be regulated by Sp1 (73).…”
Section: Discussionmentioning
confidence: 92%
“…In this regard, it is important to note that a growing body of evidence suggests that the ␣3 and ␤4 subunit genes may be coordinately expressed, whereas the ␣5 gene may be independently regulated (47, 49 -51). A number of laboratories, including our own, have identified several cis-acting transcriptional regulatory elements (52-66) and trans-acting regulatory factors (59,65,(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77) that are involved in the expression of the clustered nACh receptor subunit genes. The majority of the regulatory elements thus far described are involved in activating transcription and are located upstream of the nACh receptor genes that they regulate.…”
mentioning
confidence: 99%
“…For this purpose we chose the bovine ␣7 and the human ␤4 promoters, which had been characterized previously by us (19,20) and have different transcriptional requirements. The Sox boxes were located between the luciferase reporter gene and the mentioned promoters, and the activity of the resultant constructs in C2C12 cells was compared with that shown by the corresponding parent constructs.…”
Section: Fig 2 Rt-pcr Analysis Of ␣7 ␣9 and ␤4 Nachr Subunits Fromentioning
confidence: 99%
“…The ␤4, ␣3, and ␣5 promoters are all able to direct expression of reporters in neural cell lines, and each can be transactivated by the ubiquitously expressed family of Sp transcription factors (5,6,9,10,54,61) and the neurally restricted…”
mentioning
confidence: 99%